Middle school students' conceptual perceptions of the social studies course, and their transfer of the outcomes to daily life - İBRAHİMOĞLU, ZAFER (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
The primary aim of this study was to identify middle school students' conceptual perceptions of the social studies course, and their usage and awareness of the course outcomes in daily life. Qualitative research methods and techniques were employed in the study. The participants were 34 middle school seventh-grade students from a state middle school in Istanbul, Turkey. Letter writing was used as the data-gathering tool, and the data were analyzed by means of the content analysis technique. The findings showed that the participants perceived social studies as a course consisting of social-humanistic sciences with an emphasis on history and communication in accordance with the theoretical structure of the course, and employed their outcomes from this course that they can partly use in daily life.
Keywords: Awareness; conceptual perception; daily life; experience; social studies